The emperor's new mathematics Western learning and imperial authority during the Kangxi Reign (1662-1722) - Jami, Catherine (Oxford : Oxford University Press, 2012)
Jami explores how the emperor Kangxi solidified the Qing dynasty in 17th-century China through the appropriation of the 'Western learning', and especially the mathematics, of Jesuit missionaries. This text details not only the history of mathematical ideas, but also their political and cultural impact.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Includes bibliographical references and index.
Keywords: Science -- China -- History -- 17th century; Science -- China -- History -- 18th century; Mathematics -- China -- History -- 17th century; Mathematics -- China -- History -- 18th century; China -- History -- Kangxi, 1662-1722.; China -- Civilization -- Western influences